Real-world effectiveness and safety of ixazomib-lenalidomide-dexamethasone in relapsed/refractory multiple myeloma - Terpos, Evangelos; Ramasamy, Karthik; Maouche, Nadjoua; Minarik, Jiri; Ntanasis-Stathopoulos, Ioannis; Katodritou, Eirini; Jenner, Matthew W; Plonkova, Hana; Gavriatopoulou, Maria; Vallance, Grant D; Pika, Tomas; Kotsopoulou, Maria; et al. (Annals of hematology, 2020)
Real-world data on regimens for relapsed/refractory multiple myeloma (RRMM) represent an important component of therapeutic decision-making. This multi-centric, retrospective, observational study conducted by the treating physicians evaluated the effectiveness and safety of ixazomib-lenalidomide-dexamethasone (IRd) in 155 patients who received ixazomib via early access programs in Greece, the UK, and the Czech Republic. Median age was 68 years; 17% had an Eastern Cooperative Oncology Group performance status ≥ 2; median number of prior therapies was 1 (range 1-7); 91%, 47%, and 17% had received prior bortezomib, thalidomide, and lenalidomide, respectively. Median duration of exposure to ixazomib was 9.6 months. Overall response rate was 74%, including 35% very good partial response or better (16% complete response). Median progression-free survival (PFS) was 27.6 months (27.6 and 19.9 months in patients with 1 or > 1 prior lines, respectively). IRd treatment for ≥ 6 months was associated with longer PFS (hazard ratio 0.06). Fourteen patients (9%) discontinued IRd due to adverse events/toxicity in the absence of disease progression. Peripheral neuropathy was reported in 35% of patients (3% grades 3-4). These findings support the results of the phase III TOURMALINE-MM1 trial in a broader real-world RRMM population.
Keywords: glycin; dospělí; Lenalidomide; sloučeniny boru; lenalidomid; senioři nad 80 let; přežití bez známek nemoci; Disease-Free Survival; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; lidé středního věku; Recurrence; Middle Aged; Aged, 80 and over; míra přežití; Dexamethasone; Multiple Myeloma; mužské pohlaví; Survival Rate; Adult; Boron Compounds; recidiva; dexamethason; ženské pohlaví; Glycine; lidé; Aged; senioři; mnohočetný myelom; Male; Female